Α‐mangostin attenuates pristane‐induced lupus nephritis by regulating Th17 differentiation. (25th November 2019) - Zhou, Xiaoqing; Chen, Huanpeng; Wei, Fengjiao; Zhao, Qingyu; Su, Qiao; Lei, Yu; Yin, Meng; Tian, Xuyan; Liu, Zhonghua; Yu, Bolan; Bai, Chuan; He, Xixin; et al.
Abstract: Aim: α‐mangostin, a polyphenolic xanthone derivative of mangosteen, has been reported to possess multiple therapeutic properties, such as anti‐cancer, anti‐allergy and anti‐inflammatory activity. However, its anti‐inflammatory effects in autoimmune diseases such as lupus nephritis (LN) remain unclear. In this study, we want to investigate the therapeutic effect of α‐mangostin in LN. Methods: First, we elucidated the retinoic acid receptor related orphan receptor gamma t (RORγt) inhibitory activity of α‐mangostin in cell‐based assay and T helper 17 (Th17) differentiation in vitro assay. Then, we established a pristane‐induced LN mouse model and randomly divided these into a normal control group, model control group, α‐mangostin group and prednisone acetate group. Finally, anti‐double‐stranded DNA (anti‐dsDNA) level in serum was detected by enzyme‐linked immunosorbent assay, interleukin (IL)‐17A and interferon (IFN)‐γ expression in spleen cells by flow cytometry; histomorphology examination of kidneys was performed by periodic acid‐Schiff staining and immunofluorescence analysis with an anti‐immunoglobulin G (anti‐IgG) and anti‐IgM antibodies. Results: We found that α‐mangostin inhibited RORγt transcription activity in a cell‐based assay and also polarized Th17 cells in an in vitro induction experiment. Our results also showed that α‐mangostin could significantly decrease serum anti‐dsDNA antibody levels, IL‐17A and IFN‐γ expression and alleviate renal pathological damage in the α‐mangostin‐treated group mice than in the model group mice. Conclusion: Thus, α‐mangostin demonstrated its potential as a candidate therapeutic drug for LN and other Th17‐mediated autoimmune diseases by inhibiting the function of Th17.